DYNAMICAL LIMIT SETS OF MOTION ON TOPOLOGICAL STRUCTURE OF SET F(T,X) - Dervishi, Neki (Matematichki Bilten, 2009)
In this paper is proved that, if \(T\) is a real line and \((Y,V)\) is a Hausdorff topological space, then the dynamical limit sets \(Ω_x(A_x)\) of the motion \(ψ(x,t)\) are close and invariant on topological structure of the set \(F(T,X)\), related with the relative topology of coordinatewise convergence.